Description and Biomechanical Comparison of a Percutaneous Radiologic Gastropexy Technique in a Canine Cadaver Model. Issue 4 (18th April 2016) - Culp, William T. N.; Balsa, Ingrid M.; Kim, Sun Y.; Glaiberman, Craig B.; Grimes, Millie; Mayhew, Philipp D.; Johnson, Eric G.; Palm, Carrie A.; Garcia, Tanya C.; Kass, Philip H.
Abstract : Objective: To describe a novel percutaneous radiologic gastropexy (PRG) technique in a canine model and to biomechanically compare this technique to open incisional gastropexy (OIG) and laparoscopic‐assisted incisional gastropexy (LAG). Study Design: Randomized ex vivo biomechanical study. Animals : Canine cadavers. Methods: Fifteen cadavers were randomized to 1 of 3 surgical interventions: OIG, LAG, and PRG. For the PRG procedure, the stomach was distended with air, and a preloaded T‐fastener device was utilized to attach the stomach to the body wall with fluoroscopic‐guidance. The procedural times of the 3 techniques were recorded. After completion of the procedure, the stomach and body wall overlying the stomach wall were harvested and the maximum tensile strength of the gastropexies was determined. Results: The maximal tensile strength was not significantly different between groups. The total procedural time for the PRG procedure (5 minutes) was significantly shorter than both OIG (28 minutes) and LAG (20 minutes) procedures. Conclusion: The PRG technique described in this study demonstrated a similar maximal tensile strength to commonly employed gastropexy techniques (OIG and LAG) in an acute canine model. Additionally, the PRG procedure was significantly faster to perform. The clinical relevance of this technique will be determined by further study to assess the applicability and efficacy of this procedure in clinical patients by determining the likelihood of adhesion development and the ability of the adhesion to prevent gastric volvulus.